2007
DOI: 10.2164/jandrol.106.000067
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aneuploidy Rate in Sperm With Fragmented DNA as Determined by the Sperm Chromatin Dispersion (SCD) Test and FISH Analysis

Abstract: Previous studies suggest that sperm DNA fragmentation may be associated with aneuploidy. However, currently available tests have not made it possible to simultaneously perform DNA fragmentation and chromosomal analyses on the same sperm cell. The recently introduced sperm chromatin dispersion (SCD) test allows users to determine this relationship. Semen samples from 16 males, including 4 fertile donors, 7 normozoospermic, 3 teratozoospermic, 1 asthenozoospermic, and 1 oligoasthenoteratozoospermic, were process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 62 publications
(81 reference statements)
2
38
0
3
Order By: Relevance
“…In addition, mis-segregated chromosomes may themselves trigger the apoptotic process [Dobles et al 2000]. Sperm DNA damage may be part of a genomic surveillance mechanism to control or maintain normal production of spermatozoa and to inactivate and reject spermatozoa with altered or an unbalanced genome [Muriel et al 2007]. This theory might explain the strong relationship between aneuploidy and sperm DNA damage that we observed in our study, and as reported by others [Carrell et al 2003;Muriel et al 2007].…”
Section: Discussionsupporting
confidence: 82%
“…In addition, mis-segregated chromosomes may themselves trigger the apoptotic process [Dobles et al 2000]. Sperm DNA damage may be part of a genomic surveillance mechanism to control or maintain normal production of spermatozoa and to inactivate and reject spermatozoa with altered or an unbalanced genome [Muriel et al 2007]. This theory might explain the strong relationship between aneuploidy and sperm DNA damage that we observed in our study, and as reported by others [Carrell et al 2003;Muriel et al 2007].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, a systematic review and meta-analysis of IVF and ICSI studies shows that sperm DNA damage is associated with a significant increase in the rate of pregnancy loss after IVF and ICSI [36]. The increased rate of failed embryos and pregnancy loss associated with male factor infertility and sperm DNA damage in IVF and ICSI may be due to sperm chromosomal aneuploidy but this has not been demonstrated conclusively [7,28]. It has been suggested that the process of sperm selection during ICSI in humans may lessen the potential undesirable effects of sperm DNA damage on fertility outcomes [15].…”
Section: Discussionmentioning
confidence: 99%
“…In assisted reproduction programs, several studies show that high levels of sperm DNA fragmentation are related to lower pregnancies rates either natural or using IUI, IVF or ICSI procedures [54][55][56][57] and higher aneuploidies rates in embryos [52,58,59]. Greco et al [60] reported 29 ICSI cycles in which the percentage of DNA-fragmented spermatozoa, detected by TUNEL assay, was >15%; only two pregnancies and no births were obtained.…”
Section: Discussionmentioning
confidence: 99%